Steroids contents in waters of wastewater purification plants: determination with partial-filling micellar electrokinetic capillary chromatography and UV detection. Issue 11 (1st September 2016) - Sirén, Heli; El Fellah, Samira
ABSTRACT: Partial-filling micellar electrokinetic capillary chromatography (PF-MEKC) with UV detection was applied for determination of human-based steroids in water samples of Finnish wastewater treatment plants. The samples were purified with solid-phase extraction (SPE) on octadecyl substituted polymer sorbents obtaining analyte enrichment of 20, 000-fold. The steroids studied were androgens, estrogens, and progesterone. Three of the steroids could be quantified with the PF-MEKC method. The detection and quantification limits were 0.05–1.06 μg/mL and 0.15–3.2 μg/mL, meaning in the SPE concentrates as 2.5–53 pg/L and 7.5–160 pg/L, respectively. In the influent waters, the total amount of testosterone glucuronide, androstenedione, and progesterone was up to 350 ng/L. In effluent water samples the total steroid quantity was maximum at 320 ng/L. Remarkably high quantity of androstenedione was quantified in both influent and effluent water samples. The cleanest effluent waters were produced in Western Finland. Correspondingly, the highest quantities were located near the largest lake and river areas in South-Eastern Finland. The concentration variation in effluent waters was explained with differences in the purification materials and processes at the plants and with steroid adsorption on soil and organic material suspended into water.